2023
DOI: 10.3389/fped.2022.1089168
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopic management of mesenteric cysts in children

Abstract: BackgroundMesenteric cysts (MCs) are rare intra-abdominal masses in children, and laparoscopic complete cyst resection is still difficult. This study reviewed our experience in diagnosing and managing MCs at our center, focusing on the clinical characteristics of MCs and the effectiveness of robotic-assisted laparoscopic surgery.MethodsWe conducted a retrospective analysis of the records of all patients diagnosed with MCs and managed with robotic-assisted laparoscopic surgery at our center between February 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…After removing duplicates and title and abstract screening, 35 studies were assessed for eligibility through full-text evaluations. In the end, fifteen studies were considered eligible and included in the review ( Figure 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and title and abstract screening, 35 studies were assessed for eligibility through full-text evaluations. In the end, fifteen studies were considered eligible and included in the review ( Figure 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five out of eight studies reported LOSs (3.5 to 7.8 days), and there were very limited data on readmissions and reinterventions. There were no IOCs reported, and only one conversion (3.0%) occurred in Meehan et al’s study [ 16 , 20 , 21 , 23 , 25 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is di cult to distinguish their boundaries by the naked eye using ordinary laparoscopic instruments, and complete resection is di cult, especially in those patients it is located in the root of the mesentery. Therefore, it is di cult to perform traditional laparoscopic surgery under total laparoscopy in some patients, making it necessary to enlarge the umbilical incision or even to transfer to laparotomy to resect the diseased cysts and the bowels and perform intestinal anastomosis [15]. Although surgical trauma is still reduced compared with laparotomy, when cysts are removed for intestinal anastomosis, some bowel loops still need to be exposed outside the body, thus increasing the risk of postoperative intestinal adhesions and intestinal stula.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported laparoscopic surgeries for abdominal lymphatic malformations include two surgical approaches. One is complete laparoscopic surgery, which is widely used in adult patients with a large abdominal cavity, and the other is laparoscopic-assisted exploration to first locate and decompress the cyst of lymphatic malformations, followed by cyst excision through a slightly expanded umbilical incision, which is more commonly used in pediatric patients [ 16 , 30 32 ]. Large cysts in pediatric patients could impair surgical visualization during laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery, including robotic-assisted and laparoscopic-assisted surgery, has become an option for treating ML and OL, but previous reports are sparse with small sample sizes [ 14 16 ]. In addition, to our knowledge, no studies have systematically compared the clinical characteristics, surgical management and prognosis of ML and OL.…”
Section: Introductionmentioning
confidence: 99%